Path recovery for ad-hoc on-demamd distance 6lowpan routing protocol - Ee, Gee Keng (2013)
Internet Protocol version 6 over low power wireless personal area network (6LoWPAN) has become a new technology to provide the Internet connectivity to the traditional wireless sensor network (WSN). The introduction of 6LoWPAN adaptation layer enables header compression, packet fragmentation and reassembly,and layer-two forwarding from the network layer to media access control (MAC) layer in the 6LoWPAN protocol stack. In order to route the delivered packet from a source node (also named as originator) to a destination node, the Mobile Ad hoc Network (MANET) working group has simplified the existing Ad-hoc On-Demand Distance Vector (AODV) routing protocol for 6LoWPAN with 6LoWPAN Ad-Hoc On-Demand Distance Vector Routing (LOAD) protocol. However, the conceptual LOAD routing protocol, which currently uses the MAC address to route the packet in the personal area network (PAN), has not proposed any path recovery mechanism in 6LoWPAN. In this thesis, an originator recognition (OR) path recovery mechanism is proposed for the 6LoWPAN LOAD-based routing protocol. In the proposed OR path recovery mechanism, the participated nodes will memorize the originator address from the data packet during the data forwarding. When a link break happens on the path to a destination node, the conceptual LOAD protocol message is modified by inserting an identity key, which is the memorized originator address, in the generated route error (RERR) message and is forwarded towards the originator for the failure notification. The identity key is then used by the originator of a fail forwarded data packet to initialize path recovery during the link failure in order to retransmit the failed data packet to the unreachable destination node. Instead of using the MAC address in the LOAD routing protocol, the IP address is used in the proposed 6LoWPAN Ad-Hoc On-Demand Distance Vector Routing with Originator Recognition path recovery mechanism (OR-LOAD) routing protocol which is designed for the global routing. The developed OR-LOAD routing protocol was examined under noisy 6LoWPAN environment in Qualnet simulator. Its performance is then evaluated and compared to AODV routing protocol in terms of packet delivery ratio, throughput, average endto-end delay and average energy consumption. The simulation results show that the proposed OR-LOAD routing protocol outperforms AODV routing protocol with average of 19.4 % and 30.6 % in terms of packet delivery ratio and throughput respectively. This is because the OR path recovery mechanism in the OR-LOAD routing protocol lessens the packet loss caused by irreparable broken link and reduces the delay taken for link break handling. Thus, the results show that ORLOAD routing protocol has a higher reliability than AODV routing protocol. However, it has induced slightly higher average end-to-end delay compared to AODV routing protocol with comparable average energy consumption in both routing protocols.